Multisegment Ultra Wide Band Antenna for 5G Applications (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper presents a novel step-structured Multisegment Dielectric Resonator Antenna (MSDRA). Proposed structure is a combination of two segments with varying dielectric constants.  Microstrip feed line in combination of PEC wall is used to couple electro- magnetic energy to the radiator. Application of Perfect electric conductor excites higher order modes to the structure. Size of ground plane is reduced to create multi-mode resonance to create Ultra Wide Band antenna. Amalgamation of modes created by partial ground structure with conducting walls yields a high impedance bandwidth of 87%.  Partial ground structure along with entire ensemble provides multimode resonance which generates peak radiation efficiency of 90% throughout the operating frequency range of 3.2 GHz -8.2 GHz. Constant gain, High bandwidth and low delay makes this design extremely suitable for 5G and sub 6G frequency band. Proposed antenna is simulated on HFSS 3D simulators based on Finite Element method.